Effect of thermal aging on microstructures of aramid composites. Issue 2 (14th May 2015) - Li, Chang‐Sheng; Huang, Xian‐Cong; Yan, Li; Zhou, Hong; Shen, Zhihao; Fan, Xing‐He
Abstract : The effect of thermal aging on aramid composites was assessed in this study. Poly(vinyl butyral)/phenol formaldehyde (PVB/PF) resin was used to prepare the aramid composites, which were programmed at 70, 90, 120, and 150°C for various periods of time up to 2, 688 h. The microstructures and aging mechanisms were investigated by dynamical mechanical thermal analysis, Fourier transform infrared spectroscopy, and thermogravimetric analysis. Ballistic limited velocity of composites was determined by 1.1g Fragment projectiles. The results suggest that three microphases exist in the PVB/PF system. Each phase exhibits different aging mechanisms at different aging temperatures. Reduction of ballistic limited velocity was strongly affected by aging conditions. POLYM. COMPOS., 38:252–259, 2017. © 2015 Society of Plastics Engineers